2020
DOI: 10.1128/mbio.00398-20
|View full text |Cite
|
Sign up to set email alerts
|

Hiding in Plain Sight: an Approach to Treating Patients with Severe COVID-19 Infection

Abstract: Patients with COVID-19 infection are at risk of acute respiratory disease syndrome (ARDS) and death. The tissue receptor for COVID-19 is ACE2, and higher levels of ACE2 can protect against ARDS. Angiotensin receptor blockers and statins upregulate ACE2. Clinical trials are needed to determine whether this drug combination might be used to treat patients with severe COVID-19 infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
153
0
15

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 168 publications
(168 citation statements)
references
References 20 publications
0
153
0
15
Order By: Relevance
“…These drugs can affect the host response to infection, not the virus, especially by preventing endothelial dysfunction, a shared feature of several virus infections [14]. Their combination seemed to promote a return to homeostasis, allowing patients with Ebola virus infection to recover on their own [15].…”
mentioning
confidence: 99%
“…These drugs can affect the host response to infection, not the virus, especially by preventing endothelial dysfunction, a shared feature of several virus infections [14]. Their combination seemed to promote a return to homeostasis, allowing patients with Ebola virus infection to recover on their own [15].…”
mentioning
confidence: 99%
“…9 Statins preserve MyD88 at normal levels during hypoxia 10 and mitigate NF-jB activation, 11 so some investigators hypothesized the idea of using statins for the treatment of MERS-CoV infection 12 and COVID-19. 13 But animal studies have shown that aberrant inhibition of TLR adaptor TRIF or MyD88 signals results in severe lung damage and death. 7,14 This may be due to the compensatory activation of other innate immune factors.…”
Section: Potential Mechanistic Effects/adverse Effects Of Statins On mentioning
confidence: 99%
“…17 The findings on the effects of statin on communityacquired 18 and ventilator-associated pneumonia 19,20 are conflicting as well. Finally, for the COVID-19 outbreak, although some US hospitals included statins in COVID-19 treatment 6 and some proposed their use for this condition, 13 some others worry regarding statininduced increase in IL-18 and deterioration of SARS-CoV-2-induced ARDS and mortality. 21…”
Section: E T T E R S T O T H E E D I T O Rmentioning
confidence: 99%
“…Further, levels of ACE expression in the heart show distinct diurnal changes (32) and AngII induces changes in the expression of circadian genes in vascular cells (33), while changes in BMAL1 expression also affect the expression of angiotensinogen and resting blood pressure in perivascular adipose tissues (34) Thus, it is conceivable that lung expression of ACE2 will also manifest circadian changes through cell autonomous regulations and through indirect effects of circadian changes in reninangiotensin system. Considering that the more severe manifestations of SARS-Cov-2 infection include acute respiratory distress syndrome (ARDS), a condition characterized by enhanced vascular permeability in the lung (35,36), it would be important to also consider the role of the pulmonary endothelium and its cognate expression of ACE2 as a potential target for the virus-induced ARDS (37,38). Of note, a putative adjuvant role for melatonin has been recently proposed for ARDS in the setting of SARS-Cov-2 infection (39).…”
Section: Putative Role Of Circadian Clocks In the Pathophysiology Of mentioning
confidence: 99%